The Impact of Sustainable Tourism Perception on Accommodation Preferences: A Study on Turks Living in Germany - AKBURAK, Nihat; KÖMÜRCÜ SARIBAŞ, Simge (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Sustainable tourism is essential for protecting environmental, economic, and cultural resources for future generations. Moreover, applying sustainability practices in accommodation businesses plays a key role in managing the long-term impacts of tourism. Türkiye welcomes millions of tourists every year, making it one of the major global destinations. Within this context, Turkish citizens living in Germany represent an important target group for the tourism industry due to their cultural ties and economic contribution. Therefore, this study aims to explore how Turks living in Germany perceive sustainability when they return to Türkiye for vacation. Interviews were conducted with 20 participants, and the data were analyzed through content analysis. One notable finding indicates that participants, who demonstrate a high level of sustainability awareness in their daily lives in Germany, tend to largely overlook these values during their holidays in Türkiye. This behavior appears to be influenced by a sense of cultural comfort, the psychological relaxation associated with being on vacation, and the absence of strict social norms. Additionally, another significant finding reveals that participants primarily associate sustainability with environmental issues, while displaying limited awareness of its social and economic aspects.